Sex-related differences in mortality following an admission for acute heart failure across left ventricular ejection fraction spectrum. (14th October 2021) - Santas Olmeda, E; Palau, P; De La Espriella, R; Minana, G; Soler, M; Lorenzo, M; Nunez, G; Chorro, F J; Nunez, J
Abstract: Background: Prognosis in heart failure (HF) may differ between women and men. However, data is conflicting and sex-related differences in prognosis may be determined by left ventricular ejection fraction (LVEF) status. We sought to evaluate the prognostic differences between women and men with HF following an admission for acute HF (AHF). Methods: We included 4, 812 patients consecutively admitted for AHF in a multicenter registry from 3 hospitals in Valencia (Spain). Study endpoints were all-cause, cardiovascular (CV), and HF-related mortality at 6-months follow-up. Multivariable Cox regression models were fitted to investigate sex-related differences across LVEF status. Results: 2, 243 (46.6%) patients were women and 2, 569 (53.4%) were men. 2, 608 (54.2%) patients had HF with preserved ejection fraction. At 6-months follow-up, 645 patients died (13.4%), being 544 (11.3%) and 416 (8.6%) CV and HF-related deaths, respectively. LVEF was not independently associated to mortality risk (HR=1.02; 95% CI 0.99–1.05; p=0.135). After multivariate adjustment, we found no sex-related differences in all-cause mortality (p-value for interaction=0.168). However, a significant interaction between sex and the risk of CV and HF mortality was found across LVEF status (p-value for interaction= 0.030 and 0.007; respectively). Compared to men, women had a significant lower risk of CV-mortality and HF-mortality at LVEF<25% and <42%, respectively. On the contrary, women showed a higher risk of HF-mortality at the upper extreme of LVEF (>75%) (Figure, panel A and B). Conclusions: Following an admission for AHF, no sex-related differences were found in the risk of all-cause mortality. However, compared to men, women showed a lower risk of CV and HF-mortality at the lower extreme of LVEF. On the contrary, they showed a higher risk of HF-death at the upper extreme. Funding Acknowledgement: Type of funding sources: None.